Potret Perilaku Menyimpang dalam Novel Tiba Sebelum Berangkat Karya Faisal Oddang - Prayogi Riswanto; Zulfadhli Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2023)
The purpose of this research is to (1) describe the forms of behavior (2) describe the factors that cause deviant behavior (3) describe the impact of deviant behavior. This research is a qualitative research using descriptive method. The data collection technique was carried out in four stages, namely: (1) reading and understanding the novel in order to master the contents of the novel, (2) conducting a literature study related to deviant behavior, (3) identifying data related to forms of deviant behavior, factors that cause storing behavior , and the impact of deviant behavior, (4) inventorying data into a data inventory format. The data validation stage uses a triangulation technique. The discussion in this study includes First, the forms of deviant behavior in the novel Tiba Sebelum Berangkat by Faisal Oddang include, anti-social, extramarital sex, homosexuality, and violence. Second, the factors that cause deviant behavior in the novel Tiba Sebelum Berangkat by Faisal Oddang include unhealthy mental attitudes, feelings of disappointment, and deviant learning processes. Third, the impact of deviant behavior in the novel Tiba Sebelum Berangkat by Faisal Oddang includes crime and the fading of values and norms